Recanalization of long iliac occlusions by humeral and radial approach- About 30 cases - Aabdou A; Ezzahraoui MR; Almahraoui O; Alaoui M (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2019)
Background: Complex stenosis and iliac occlusions (TASC C-D) often require surgical revascularization. Since 2007, several studies have studied the performance of endovascular revascularizations via brachial or radial anterograde approach with a good success rate. Material and methods: We performed a retrospective and analytical study, comprising a series of 30 patients who underwent an endovascular treatment within the vascular surgery department of the Military Hospital Avicenna of Marrakech Morocco between January 2014 and February 2016 Results: During the study period, 30 patients were included. The average age of our patients was 61.8 years (42 to 83 years). We noted a male predominance with a sex-ratio M / W of 2.7. All having as risk factors cardiovascular: age, sex and smoking. The distribution of iliac lesions was dominated by primary iliac occlusions and the right iliac axis (70%) according to the TASC 2 classification; occlusions were classified as TASC C in 10 patients (33.3%) and TASC D in 20 patients (66.6%). We haddilated the occlusion by angioplasty introduced by the humeral way in 20 patients and radial in 10 patients, with placement of a stent. The success of the technique was obtained in 100% of the cases. Conclusions: Brachial and radial access for TASC C-D aortoiliac chronic occlusion improves the technical success rate without the need for reentry devices and remains a better option for patients at risk treatment.